Regulating Biogas Power Plant From Palm Oil Mill Effluent (POME): A Challenge to Indonesia's Just Energy Transition - Prischa Listiningrum; Siti Hafsyah Idris; Sri Suhartini; Dwima Vilandamargin; Sherlita Nurosidah (Yustisia, 2022)
Palm Oil Mill Effluent (POME) is a potential source of bioenergy but it is also known as one of the biggest emission's contributor from palm oil industry thus capturing the produced methane (CH4) is necessary in creating a sustainable energy for the environment. This article examines current regulations of generating electricity from POME. The aim is to promote renewable energy deployment in Indonesia in order to support the just energy transitions to a low carbon economy. This study initially looks at the existing regulations by using legal doctrinal and socio legal research. Afterwads, interviews are conducted to the palm oil industry in order to explore potential threats in developing this source of energy. The main findings suggest that there are number of government interventions needed to support the construction of POME based biogas power plant, such as providing a scheme of green loans, adjusting the feed-in tariffs and revising the grid systems, imposing incentives for carbon reduction, and applying the power purchase agreement. In addition, increasing public perception to combat the climate change by moving significantly to a low carbon economy is critical to fostering the 2030’s emission reduction target.